2020
DOI: 10.1038/s41598-020-72351-6
|View full text |Cite
|
Sign up to set email alerts
|

Key factors behind autofluorescence changes caused by ablation of cardiac tissue

Abstract: Radiofrequency ablation is a commonly used clinical procedure that destroys arrhythmogenic sources in patients suffering from atrial fibrillation and other types of cardiac arrhythmias. To improve the success of this procedure, new approaches for real-time visualization of ablation sites are being developed. One of these promising methods is hyperspectral imaging, an approach that detects lesions based on changes in the endogenous tissue autofluorescence profile. To facilitate the clinical implementation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, MRI imposes additional cost for compatible equipment. Other groups have demonstrated intraoperative tracking of non-irrigated lesion formation using hyperspectral autofluorescence imaging 11 , 26 , photoacoustic 18 , 55 57 , and optical coherence tomography (OCT) 15 , 19 , 22 25 . Previously, our group demonstrated lesion depth estimation up to 4 mm using NIRS 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MRI imposes additional cost for compatible equipment. Other groups have demonstrated intraoperative tracking of non-irrigated lesion formation using hyperspectral autofluorescence imaging 11 , 26 , photoacoustic 18 , 55 57 , and optical coherence tomography (OCT) 15 , 19 , 22 25 . Previously, our group demonstrated lesion depth estimation up to 4 mm using NIRS 12 .…”
Section: Discussionmentioning
confidence: 99%
“…OCT-integrated catheters enabled real-time imaging feedback to identify tissue structures and direct monitoring of RF lesion formation, ex vivo 19 , 22 24 and in vivo 15 , 25 . Recently, acute necrotic areas in atrial tissue were identified using hyperspectral imaging system based on ultraviolet-excited tissue autofluorescence 11 , 26 28 . Another promising technique, near-infrared spectroscopy (NIRS), uses broadband light to interrogate tissue volumes deeper than OCT and ultraviolet-excited tissue autofluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…One area which has been particularly closely investigated is the development of methodologies for the visualisation of radiofrequency ablation lesions to improve the treatment of atrial fibrillation, which has a high frequency of recurrence due to incomplete destruction of tissue [20,[32][33][34][35][36][37]. Application of the assessment of autofluorescence to this clinical problem has been hampered by the presence of thick interwoven layers of autofluorescent collagen and elastin in the left atrium of the heart, which is the most frequent source of the aberrant bioelectrical activities that cause arrythmias.…”
Section: Cardiac Assessmentmentioning
confidence: 99%
“…Several groups have adopted optical methods to directly visualize lesion delivery and to predict lesion dimensions [14][15][16]. Catheter based optical coherence tomography (OCT) allows immediate imaging feedback to monitor RF lesion formation [14,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Autofluorescence hyperspectral imaging (HSI) is another optical modality that has demonstrated both identification of scar and location of ablated tissue. HSI illuminates ultraviolet (UV) light on to the tissue surface and analyze the reflected light within the excitation range [15,[25][26][27][28]. RF ablated tissue has shown loss in the major endogenous fluorophore inside viable cardiomyocytes are nicotinamide adenine dinucleotide (NADH) and increase in diffuse reflectance.…”
Section: Introductionmentioning
confidence: 99%